Gait Parameters Affecting the Perception Threshold of Locomotor Symmetry: Comment on Lauzière, et al. (2014). Issue 2 (October 2014) - Hoogkamer, Wouter; Bruijn, Sjoerd M.; Duysens, Jacques
In a recent work on locomotor symmetry while walking on a split-belt treadmill, Lauzière and co-workers determined the perception threshold of gait symmetry in a sample of healthy elderly. In addition, they aimed to determine which particular gait parameters affect the symmetry of the perception threshold. Although only temporal and kinetic gait parameters were measured (and no kinematics), it was suggested that stance time symmetry is an important criterion that participants use to identify the threshold. Here it is argued that several other gait parameters could qualify equally well as main criteria used to identify the threshold and that these parameters should be taken into account in future studies.